Taxa básica de juros, competição bancária e spread nas operações de crédito para pessoas físicas no Brasil: uma análise teórica e empírica - Pirtouscheg, Lívia Abrão Steagall (2014)
The debate and the politics surrounding the strategy of bank spread reduction in Brazil has been extended for a very long time and was fundamentally concentrated in macroeconomics aspects. This dissertation has the goal of evaluate the new policy of bank spread reduction implemented by the federal government, which has added microeconomic aspects to this tendency. In order to do so, a mathematical model was presented that combines microeconomics aspects, such as was developed by Nakane (2001), with macroeconomics aspects, originally presented by Ho & Saunders (1981). This model was tested for the 25 largest banks in the period of March 2009 through March 2013, using the Panel Data Methodology. The GMM System model was the one that best fitted the data gathered and the results showed that both aspects are relevant in explaining the bank spread in Brazil, since both the interest rate and competition were significant. Therefore, one must avoid analyzing the determinants of bank spread separately, as is frequently made in the literature, considering the econometric problems related to the bias from the omission of relevant variables. Furthermore, as a policy proposition, it is defended the escalation of the actions recently chosen by the federal government in order to fight against the elevated rates of bank spread practiced in the country.